The influence of bed-sharing on infant physiology, breastfeeding and behaviour: A systematic review. (February 2019) - Baddock, Sally A.; Purnell, Melissa T.; Blair, Peter S.; Pease, Anna S.; Elder, Dawn E.; Galland, Barbara C.
Summary: This review aimed to better understand the underlying physiology of the risks and benefits of bed-sharing. Eight databases were searched using terms relating to adult–infant/baby, bed-sharing/co-sleeping combined with outcome terms for physiology, sleep, cardiovascular, respiratory, temperature and behaviour. Of 836 papers identified, 59 papers representing 48 cohorts met inclusion criteria. Objective data using various methodologies were available in 27 papers and subjective data in 32 papers. Diverse measures were reported using variable definitions of bed-sharing. Identified physiological and behavioural differences between bed-sharing and cot-sleeping included increased behavioural arousals, warmer in-bed temperatures and increased breastfeeding duration in bedshare infants as well as differences in infant overnight sleep architecture, cardiorespiratory control and cortisol responses to stress. We concluded that many differences are context-specific, and dependent on the subjective view of the parents and their cultural values. Objective risk arises if the infant is unable to mount an appropriate physiological or behavioural response to their micro-environment. More studies in the bed-sharing setting are needed to identify infant risk, the potential benefits of a safer environment, and how bed-sharing interacts with infant care practices other than sleep.